Studying acute toxicity of the lipophilic extractions from Tagetes L. containing carotenoids - E. А. Malugina; А. V. Mazulin; I. F. Belenichev; G. P. Smoylovskaya (The State Expert Center of the Ministry of Health of Ukraine, 2018)
Marigold (Tagetes L.) is species of plants widely spread all over the world which is used in folk medicine for treating gastro-intestinal and infectious diseases. Multicomponent chemical composition assures large-scaled therapeutic action for the medicines obtained. Extractions and biological active substances from Marigold (Tagetes L.) as a promising source for new vegetable medicines attract attention of scientific community. Therefore, studying acute toxicity in lipophilic extractions from Tagetes L. is of great scientific and practical significance. The aim of this research was studying acute toxicity in lipophilic extractions from Tagetes patula L., undersized, brand Goldkopfen and Tagetes erecta L., high-sized, brand Hawaji in epicutaneous application and intragastric administration. The samples for research have been obtained from Tagetes dried raw material by extraction with corn oil refined and deodorized. The research has been carried out on white non-standard rats according to the Ukrainian legislation. Single external application of the sample in dosages 0.7500ml/cm², 0.3750ml/cm², 0.1875ml/cm² was used to assess toxicity. Studying acute toxicity in intragastric administration has been performed by Litchfield-Wilcoxonу technique on three linear groups of animals. To attain higher dosages the samples have been introduced repeatedly at intervals 30 minutes within 120-180 minutes. During experiment no statistically reliable changes in behavior and general condition in animals have been noted. Pathomorphologic examination revealed no deviations in structure and mass indices for internal organs. It has been determined that lipophilic extractions from inflorescences of Tagetes patula L., undersized, brand Goldkopfen and Tagetes erecta L., high-sized, brand Hawaji are nontoxic both in intragastric administration in limiting dosage and in epicutaneous application, therefore they can be attributed to the VI class of toxicity and they are suitable for obtaining vegetable medicines.